Daily patient flow unevenness in different sized delivery hospitals – An 11-year register study of 610 227 deliveries. (November 2021) - Vilkko, Riitta; Räisänen, Sari; Gissler, Mika; Stefanovic, Vedran; Heinonen, Seppo
Highlights: Hospital level unevenness in daily patient flow has not been studied before. Data with large sample size were collected from a well-established Medical Birth Register. Variation in relative daily delivery volume by hospital size is considerable. Daily patient flow unevenness appeared to be more prominent in the smaller delivery hospitals. Smaller hospitals had a greater risk for both low and high patient flow days compared to larger ones. Daily patient flow was optimal >90% of the days in the largest delivery hospitals. Daily patient flow unevenness is a potential quality indicator of perinatal care. Abstract: Objectives: To describe the unevenness in daily patient flow (quiet, optimal and busy days) in different sized delivery hospitals. Study design: Population based register-study of 610 227 hospital deliveries. Data were collected from the Finnish Medical Birth Register from 2006 to 2016. Delivery hospitals (N = 26) were stratified into four categories by annual delivery volume: C1 <1000, C2 1000–1999, C3 2000–2999, C4 ≥3000. Uneven daily patient flow was defined based on the mean of daily delivery volume for each hospital category: quiet day (≤50% of the mean), optimal day (>50% of the mean to <two times the mean) and busy day (≥two times the mean or more). Results: The mean of daily delivery volume varied from 2.0 to 12.6 between the smallest and the largest hospital, respectively in hospital categories C1 and C4. The daily delivery volume was optimal in 41.2%, 68.3%, 84.0%, and 91.0% of the days in hospital categories C1, C2, C3, and C4, respectively. In the smallest hospitals (C1) almost half of the days appeared to be quiet (42.9%) whereas in the larger hospitals approximately one in four (25.4%), one in seven (13.6%), and less than one in ten of the days were quiet, in the categories C2, C3, and C4 respectively. Busy days were most common in the smallest hospitals (C1) where one in six of the day (15.9%) had daily delivery volume ≥two times the mean or more. In the other hospital categories busy days were rare, and the lowest in the largest hospitals. Conclusions: Unevenness in daily patient flow was more prominent in the smaller delivery units compared to larger ones. Quiet and busy days both caused challenges to delivery unit organisations. During quiet days, fully over-resourcing of staffing occurred whereas during busy days there was a risk of under-resourcing. It is possible to optimise the size of delivery units to minimise the variation of the daily patient flow to decrease the number of quiet and busy days.